2010
DOI: 10.1598/rt.64.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effective Academic Vocabulary Instruction in the Urban Middle School

Abstract: In urban middle schools, educators find it challenging to meet the literacy needs of the many struggling readers in their classrooms, including language‐minority (LM) learners and students from low‐income backgrounds. One strategy for improving these students' reading comprehension is to teach essential academic vocabulary in a meaningful, engaging, and systematic way. This article describes the development and evaluation of an academic vocabulary curriculum for sixth‐grade mainstream classrooms with large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 19 publications
0
26
0
6
Order By: Relevance
“…They concluded that this approach to vocabulary instruction was inadequate for helping students acquire the number of new words needed to succeed as readers and learners. Contemporary programs for teaching words and meanings follow findings reported by the NICHD () and recommend explicit vocabulary instruction that teaches a few words very well, with 12 or fewer words targeted for in‐depth instruction each week (Allington, ; Armbruster, Lehr, & Osborne, ; Cunningham, ; Kelley, Lesaux, Kieffer, & Faller, ; Lesaux, Kieffer, Faller, & Kelley, ). These conservative approaches to teaching vocabulary have been embedded in many basal reading programs that administrators and teachers are encouraged to implement with fidelity, making explicit vocabulary instruction of very few words per day and week the focus of, and, in some cases, the only form of vocabulary teaching and learning experienced by students in elementary grades.…”
Section: Introductionmentioning
confidence: 92%
“…They concluded that this approach to vocabulary instruction was inadequate for helping students acquire the number of new words needed to succeed as readers and learners. Contemporary programs for teaching words and meanings follow findings reported by the NICHD () and recommend explicit vocabulary instruction that teaches a few words very well, with 12 or fewer words targeted for in‐depth instruction each week (Allington, ; Armbruster, Lehr, & Osborne, ; Cunningham, ; Kelley, Lesaux, Kieffer, & Faller, ; Lesaux, Kieffer, Faller, & Kelley, ). These conservative approaches to teaching vocabulary have been embedded in many basal reading programs that administrators and teachers are encouraged to implement with fidelity, making explicit vocabulary instruction of very few words per day and week the focus of, and, in some cases, the only form of vocabulary teaching and learning experienced by students in elementary grades.…”
Section: Introductionmentioning
confidence: 92%
“…This category includes articles that discuss learners who have English as a second language such as Wishart and Green (2010), Milbourne (2002), Kelley et al (2010) and Brooks-Wilson (2012 (Knox, 1987), immigrants (Rudd and Zacharia, 1998) and traveller communities (Ntloedibe-Kuswani, 2008). Interestingly, various methods were offered to engage these 'hard to reach' cultural minorities.…”
Section: Undereducatedmentioning
confidence: 99%
“…Wandersee () reminds us “not every term in a textbook, for instance, is of equal conceptual weight” (p. 346). But all science students can benefit from continuous exposure to carefully selected essential science terms (Kelley et al, ). Examples of selected science terms are predict, infer, model, demonstrate, tentative, evidence , and observe/observation .…”
Section: Recommendationsmentioning
confidence: 99%
“…Further, Piercey () said “probably the most difficult of all of the languages in the upper grade curriculum are those of the various sciences, botany, biology, chemistry, and physics” (p. 484), and she goes on to say “For those who elect the course known as general science, the language barriers are sometimes unsurmountable” (p. 484). In a study of urban middle schools, Kelley, Lesaux, Kieffer, and Faller () found that academic vocabulary “is a particular source of difficulty for students who struggle with comprehension” (p. 5), and this also applies to ELLs and disadvantaged native speakers who are struggling readers. They point out that such readers tend to be “word callers,” which are students who can read print but without understanding what they are reading.…”
mentioning
confidence: 99%